p–ϕ femtoscopic correlation analysis using a dynamical model - Kuroki Kenshi; Hirano Tetsufumi (EPJ Web of Conferences)
We analyse the p–ϕ correlation functions in high-multiplicity proton+ proton collisions at the LHC using a dynamical model, DCCI2, and discuss the effects of collision dynamics on the p–ϕ femtoscopic study. Collision dynamics, such as collective expansion and hadronic rescatterings, leads to the relative momentum-dependent non-Gaussian source functions. This results in deviations in the correlation functions compared to those using the Gaussian source function adopted in existing studies. Our analysis shows the importance of using the source functions that reflect more realistic collision dynamics for future precision analysis of hadron interactions via femtoscopy.